Potency of green chiretta (Andrographis paniculata) leaf extract on antibody titers of laying chickens in the starter phase - Darmansyah Darmansyah; A Mujnisa; Wempie Pakiding (Universitas Sebelas Maret, 2024)
Objective: Andrographolide, biological component, is present in Green chiretta (Andrographis paniculata), as an immunomodulator and feed additive for laying hens, has been potential to be explored. The objective of this study is to investigate the impact of green chiretta (Andrographis paniculata) leaf extract on the levels of antibodies against Avian Influenza (AI) and Newcastle Disease (ND) in laying hens during the initial phase of egg production.Methods: A total of 100 Isa Brown strain laying hens were were used ini this study consisted of 20 box cages with 60x50x50 cm. The study employed a completely randomised design (CRD) with 5 treatments, i.e. T0 = Drinking water without EEGC, T1 = Drinking water + 0.5% EEGC, T3 = Drinking water + 1% EEGC, T4 = Drinking water + 1.5% EEGC, T5 = Drinking water + 2% EEGC. The study was replicated four times for each treatment.Results: The analysis of variance revealed that the treatment with green chiretta leaf extract did not show a significant impact on AI and ND antibody titers at 3, 4, and 5 weeks of age. However, this treatment significant affect on AI and ND antibody titers at 6 weeks of age.Conclusions: The addition of green chiretta (Andrographis paniculata) leaf extract to drinking water boosts up the development of AI and ND antibody levels. It exhibited superior antibody levels in comparison to the control treatment. To clarify, applying green chiretta (Andrographis paniculata) leaf extract to drinking water can maintain AI and ND antibody levels.